- #1

karush

Gold Member

MHB

- 3,269

- 5

\tiny{b.2.1.23}

1000

Solve the initial value problem and find the critical value $\displaystyle a_0$ exactly.

$\displaystyle 3y'-2y=e^{-\pi/2}\quad y(0)=a$

divide by 3

$\displaystyle y'-\frac{2}{3}y=\frac{e^{-\pi/2}}{3}$

with integrating factor $\displaystyle e^{-2t/3}$ multiply through

$\displaystyle e^{-2t/3}y'-\frac{2}{3} e^{-2t/3}y=\frac{e^{-\pi/2}}{3}e^{-2t/3}$

ok just seeing if this is going in the right direction

1000

Solve the initial value problem and find the critical value $\displaystyle a_0$ exactly.

$\displaystyle 3y'-2y=e^{-\pi/2}\quad y(0)=a$

divide by 3

$\displaystyle y'-\frac{2}{3}y=\frac{e^{-\pi/2}}{3}$

with integrating factor $\displaystyle e^{-2t/3}$ multiply through

$\displaystyle e^{-2t/3}y'-\frac{2}{3} e^{-2t/3}y=\frac{e^{-\pi/2}}{3}e^{-2t/3}$

ok just seeing if this is going in the right direction

Last edited: